Analisis Lingkungan Kerja dalam Meningkatkan Kinerja Pegawai pada Dinas Perindustrian dan Perdagangan - Asyifa, Asyifa; Mulyadi, Dedi; Sungkono, Sungkono (Masyarakat Ekonomi Syariah Bogor, 2024)
The purpose of the research is to analyze and find out the role of the work environment in strengthening employee performance in the Karawang industry and trade office, as well as to explore the problems and solutions that can benefit the organization. The method used in this study is a qualitative descriptive method, using triangulation techniques with observation methods, data sources and interviews. The population in this observation is all employees of the Karawang industry and trade office. The sample in this observation consisted of three informants: leaders, secretaries, and employee staff. The results of this study show that the data obtained from the observations and interviews about the work environment could be better because the employee service facilities are not complete. This can result in a decrease in employee performance achievement.